Strategi Pemasaran Produk Café Batu Jimbar Sanur dalam Meningkatkan Kunjungan Wisatawan - Dwi Kristina Aryani, Ni Kadek; Sutarya, I Gede; Laksana, Putu Kussa (PARIWISATA BUDAYA: JURNAL ILMIAH AGAMA DAN BUDAYA, 2019)
Based on this research, Café Batu Jimbar has a pretty good potential but tourists visiting the Café Batu Jimbar are still not optimal because of the intense competition in the culinary field, so that Café Batu Jimbar should be able to face competition by making superior product marketing strategies. So, this research aims to determine the marketing strategy of Café Batu Jimbar Sanur product in increasing tourist visits. The method used in this research is descriptive qualitative and quantitative descriptive methods using descriptive analysis or descriptive statistics. Data collected through observation, interviews, questionnaires, literature study, and documentation. Then the data were analyzed using IFAS and EFAS matrix analysis and SWOT analysis. The results of this study indicate that the products offered at the Café Batu Jimbar are quite diverse, the product marketing strategy used by the Café Batu Jimbar has disadvantages such as the products offered more to foreign tourists, besides that the strengths of Café Batu Jimbar have cooperation with the travel agent so that it helps in increasing tourist visits, as well as unfavorable tourist perceptions of the relatively expensive prices of food and beverage products. Therefore, the marketing strategy of  Café  Batu  Jimbar  Sanur  products  in  increasing  tourist  visits  is  recommended  using alternative strategies that have been formulated in this research.Keywords: Product Café, Marketing Strategy, Tourist Perception